Effects of computer-generated patterns with different temporal and spatial frequencies on choroidal thickness, retinal dopamine and candidate genes in chickens wearing lenses - Liu, Hong; Schaeffel, Frank; Feldkaemper, Marita Pauline (Frontiers in Medicine, 2024)
Purpose Changes in choroidal thickness (ChT) are proposed to predict myopia development but evidence is mixed. We investigated time courses of choroidal responses, following different types of dynamic artificial stimulation in chicks with and without spectacle lenses, as well as changes in retinal dopamine metabolism and expression of candidate genes. Methods Chicks were kept in an arena surrounded by computer monitors presenting dynamic checkerboard fields of small, medium and large size. Fields were displayed with different cycle frequencies, as ON (rapid rise, slow decay) or OFF (slow rise, rapid decay) temporal luminance profile. Refractive errors, ocular biometry and ChT were assessed. Dopamine metabolism and candidate gene expression levels were also measured. Stimuli were applied for (1) 3 h with no lens, (2) 3 h and monocular treatment with −7D or +7D lenses, (3) 3 or 7 days. Results (1) The smallest fields caused the largest decrease in ChT. (2) Negative lens treatment induced on average 11.7 μm thinner choroids. ChT thinning was enhanced by 10 Hz-ON medium field size flicker which also reduced choroidal thickening with positive lenses. (3) With prolonged treatment, the choroid recovered from initial thinning in all groups although to varying degrees which were dependent on stimulus parameters. Relative ChT changes were positively correlated with the vitreal level of dopamine metabolites. Retinal EGR-1 mRNA level was positively correlated with choroidal thickness. Retinal melanopsin mRNA was increased by 10 Hz-ON stimulation and choroidal BMPR1A mRNA increased with 10 Hz-OFF stimulation. On average, early choroidal thinning did not predict the amount of negative lens-induced eye growth changes after 7 days, whereas later ChT changes showed a weak association. Conclusion Negative lenses caused long-lasting choroidal thinning, with some recovery during lens wear, especially after stimulation with 10 Hz. The dynamic stimuli modulated choroidal thinning but effects were small. There was little difference between ON and OFF stimulation, perhaps because the checkerboard patterns were too coarse. 10 Hz cycle frequency increased dopamine release. Less dopamine was correlated with thinner choroids. Result do not exclude a predictive value of choroidal thickening for future refractive development since we almost exclusively tested choroidal thinning effects.